Ministry of trade and industry decree no 105 of the year 2014 suspending the import of motorcycles tuk-tuks and their components - Egypt (2025)
Ministry of trade and industry decree no. 105 of the year 2014 suspending the import of motor cycles, Tuk-tuks, and their components – وزراة التجارة والصناعة قرار رقم 105 لسنة 2014 بوقف استيراد الدراجات النارية والتوك توك ومكوناتهما